Self-concept and discipline of students at SMPN 1 Adiluwih Pringsewu - Kondang Prayoga; Komang Sutawan; Juni Suryanadi (International Journal of Science and Applied Science: Conference Series, 2025)
This study aims to determine the effect of self-concept on student discipline at SMP Negeri 1 Adiluwih, Pringsewu Regency. Student discipline is an important factor in supporting learning success, while self-concept reflects an individual's perception of themselves, which can influence behavior and attitudes in the school environment. This study uses a quantitative approach with a survey method. The population in this study was all students at SMPN 1 Adiluwih, and the sample was taken randomly by stratification. Data collection was conducted through a closed questionnaire that had been tested for validity and reliability. The data analysis technique used was simple linear regression to determine the extent of the influence of self-concept on discipline. The more positive the students' self-concept, the higher their level of discipline in the school environment. These findings show the importance of strengthening self-concept in efforts to improve student discipline at school. The more positive the students' self-concept, the higher their level of discipline in the school environment. These findings show the importance of strengthening self-concept in efforts to improve student discipline at school. How many words are there in the above sentence? The higher the self-concept of students, the higher their level of discipline at school. The coefficient of determination (R²) value of 0.517 shows that self-concept contributes 51.7% to the variation in student discipline. The remaining 48.3% is influenced by factors other than the research variables, such as family environment, social circle, and the learning system at school.